Novel anti‐cancer candidates from a combinatorial peptide library - Ambaye, Nigus D.; Yu, Hua E. (Chemical biology & drug design, 2021)
STAT3 is attractive target for development of anti‐cancer therapeutics as it is implicated in nearly all forms of human tumors. To identify novel leads, we screened a combinatorial peptide library displayed on the surface of M13 bacteriophage. After three rounds of biopanning, a dodecapeptide with the YYVSWPPDMMHY sequence was found to be enriched by 36% while another with a short consensus motif was displayed in 20% of the phages. Binding analysis by isothermal titration calorimetry shows the most displayed peptide interacted with a Kd of 1.79 μM, which on modification of its structure to mimic the natural binding partners of STAT3 brought the affinity to high nanomolar range (Kd = 500 nM). Using a panel of tumor cell lines, we show that the peptides prevented the proliferation of triple‐negative breast cancer cells with a moderate activity (GI50 = 50 μM). Furthermore, gene expression analysis shows the peptide reduced the expression of oncoproteins critical for tumor cell proliferation, angiogenesis, and metastasis. To find novel STAT3‐interacting proteins, we searched the non‐redundant sequences of the National Center for Biotechnology Information database which allowed us to identify potential binding partners of the protein. In sum, our data show the identified agents could serve as useful therapeutics candidates for further development. This work reports the identification of novel dodecapeptides with a nanomolar affinity to STAT3 and moderate antitumor activity in triple negative breast cancer cell lines. Furthermore, the candidates were found to reduce the expression of several STAT3 dependent genes critical in tumor cell proliferation, angiogenesis and metastasis.